Criminal Law Enforcement for Children Who Perpetrated Hit-and-Run Accidents Resulting in Death in Traffic Accidents (Case Study Number 19/Pid.Sus-Anak/2024/PN.Mks) - Nugra Ardiansyah; Sugih Ayu Pratitis (Civiliza Publishing, 2026)
A traffic accident is a sudden and unintentional incident on the road, involving a motorized vehicle and other road users, and causing human casualties and property damage. This study aims to analyze the enforcement of criminal law against children as perpetrators of hit-and-run accidents that result in death in traffic accidents. The research method used is a normative juridical approach with qualitative data analysis. The results show that the handling of children who commit hit-and-run crimes in Indonesia is regulated by Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which emphasizes the principles of restorative justice, diversion, and the protection of children's rights. The role of parents, law enforcement officers, and the government is very important in prevention and response efforts. In practice, judges tend not to impose detention sentences to prevent children from being imprisoned.